Understanding John Rechy - DeGuzmán, María (Understanding contemporary American literature., 2019)
"John Rechy--El Paso, Texas-born novelist, essayist, memoirist, dramatist, and literary critic of Mexican and Scottish descent--published his debut novel City of Night in 1963. This controversial first novel 'remained on the New York Times bestseller list for 25 weeks, ' was translated into more than a dozen languages, become an international bestseller, and is widely recognized as 'a great American novel' and a modern classic. Rechy has gone on to publish fourteen more novels (one of them classified as a 'documentary' and not always recognized as a novel), one memoir, and a collection of forty-five essays as well as write at least three plays, one feeding into a novel and two of them based on already existing novels.2 He is still writing from his home in Los Angeles"--